2017
DOI: 10.1007/s00466-017-1402-7
|View full text |Cite
|
Sign up to set email alerts
|

A-posteriori error estimation for the finite point method with applications to compressible flow

Abstract: Aquesta és una còpia de la versió author's final draft d'un article publicat a la revista Computational mechanics. Abstract. An a-posteriori error estimate with application to inviscid compressible flow problems is presented. The estimate is a surrogate measure of the discretization error, obtained from an approximation to the truncation terms of the governing equations. This approximation is calculated from the discrete nodal differential residuals using a reconstructed solution field on a modified stencil o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…Meshless methods include SPH, the mesh-free method [147], the finite point method [148,149], and the Galerkin meshless method [150]. The common feature of the meshless methods is that the local approximation of the function that is being searched for is based only on the values of this function at individual selected points in the area.…”
Section: Meshless Methodsmentioning
confidence: 99%
“…Meshless methods include SPH, the mesh-free method [147], the finite point method [148,149], and the Galerkin meshless method [150]. The common feature of the meshless methods is that the local approximation of the function that is being searched for is based only on the values of this function at individual selected points in the area.…”
Section: Meshless Methodsmentioning
confidence: 99%
“…In this work, the local time step approach is used. When handling essentially steady problems, the temporal discretisation can directly follow Equation ( 20) by dropping the first level of discretisation in Equation (19).…”
Section: Implicit Temporal Discretisationmentioning
confidence: 99%
“…For aerodynamic modelling, earlier studies [9][10][11]18,19 have demonstrated the potential of collocation-based mesh-free methods in handling complex geometries and flow conditions. However, to promote these methods within the CFD community and fulfil their potential, significant research and development on algorithms, and on complementary techniques, for example, point cloud generation and adaptation, collocation/stencil search, implicit time marching, and especially the handling of flow conservation, are still necessary.…”
mentioning
confidence: 99%
“…Theoretical error estimations for the FPM have been established in References [37][38][39]. Due to these features, the FPM has been applied to many scientific and engineering problems such as fluid mechanics problems [32,40,41], interface problems [42,43], computational finance [39,44], Josephson junctions [45], two-dimensional nonstationary incompressible Boussinesq equations [46] and inverse heat conduction problems [47,48]. In addition, various improvements of the MLS approximation, such as the improved MLS [49], complex variable MLS [50] and interpolating MLS [51] and the corresponding meshless methods have been developed in recent years [24].…”
Section: Introductionmentioning
confidence: 99%